Effects of Environmental Change on the Habitat of Migratory Bird Species: Kesan Perubahan Persekitaran Terhadap Habitat Spesies Burung Berhijrah - Tuan Azlan, Tuan Ainul Asyikin; Abd Rahman, Azimah (Journal of Techno-Social, 2020)
The mangrove area around Teluk Air Tawar and Kuala Muda are one of the stopover locations for a variety of migratory bird species. However, migratory birds in this area are now classified as endangered species by the International Union for Conservation of Nature (IUCN) due to the decline of bird population over the years. The Development activity and changes of shoreline area for industrial and housing, global climate change, natural disasters, illegal hunting and pollution around mangrove forests have led to declining of this bird species. This study focuses on the impact of excessive land use on local economic activities and environmental changes on migratory bird habitat around the study area. Spatial basedtechnology approach through the geographic information system (GIS) applications is used to understand and identify the effects of land use on the distribution of migratory bird populations especially in their habitat selection. The results show that different land used activities have different impact on the distribution of migratory bird populations. This study is important in assisting the preservation and preservation of a location that was identified as important habitat for migratory bird species to ensure the continually visit in the future Keywords : mangrove, landused, migratory bird, distribution, habitat